The extent of citizens’ knowledge of preservatives and their health effects - H. Obaid, Zhraa; S. Alhasan, Huda; AlKhawaldeh, Ahmad (International Journal of Psychosocial Rehabilitation, 2024)
Food technology has witnessed remarkable progress during the past decades through the manufacture of various types of food additives, which are estimated at 2500 types added to food to become better specifications in terms of: nutritional value, color, flavor and stability, so it is very important to know the effect of preservatives that are added to food during conservation operations Without damage for a temporary or permanent period. This study aims to identify preservatives (their uses and risks) from the consumer point of view and to verify the extent of citizens’ knowledge of the basic variables related to the acceptance of food additives. To achieve the goals of the study, an electronic questionnaire consisting of more than (60) questions was downloaded across all social media, the site of the University of Babylon and the College of Basic Education, with the participation of (105) people. The questionnaire included nine axes consisting of: general information about preservatives and their types, industrial preservatives, how to preserve food, its harms, alternatives, pharmaceutical preservatives, preservatives in juices and finally barbic acid. The SPSS program was used to statistically analyze the questionnaire data. The results showed that the cognitive assessment of preservatives by participants was average based on the values of the standard deviation and the mean of the mean (0.421 -1.615) and (1.25- 3.05), respectively, as well as the values of the standard deviation The mean of harm to the use of preservatives in food was recorded: (0.925), (1.69), which indicates that the mean cognitive level of people participating in the questionnaire.The value of the significance level (α ≤0.05) showed that there were no statistical differences about the opinions of participants on the importance or lack of preservatives, and therefore the citizens’ awareness about the use of preservatives in food falls on individuals and relevant government institutions, as well as intensifying studies and research that show the facts of use All preservatives in all foods